Properties of chitosan matrix composites with hydroxyapatite and carbon nanotubes, and their use in bone tissue engineering - Correia, João Victor Freitas Barros; Correia, Matheus Freitas Barros (Archives in Biosciences & Health, 2019)
There is a growing demand for bone grafts by various clinical sectors, such as aesthetic procedures, treatment of injuries and dentistry, the use of synthetic materials is shown to be good due to the availability and the reduction of risks that their use brings, among the materials that are used in the clinic can be cited the chitosan matrix composites (CHI) with hydroxyapatite (HA) and carbon nanotubes (CNTs), which uses materials that are already used in the clinic HA and CHI with an innovative material in the sector the CNTs. The aim was to analyze and compare data from the current state of the art of CHI matrix composites with HA and CNTs applied in bone tissue engineering. This study is based on a review of the specialized literature on articles in online scientific journals, with thematic issues related to the properties of the biocomposite on board. The influence of the use on the composite properties generated by the use of CNTs together with the HA in the CHI matrix, for biomedical applications, more specifically in bone tissue engineering, was observed. It was observed that with subtle increases of CNTs in the CH composite Ha composites, the bioactivity, osteoconduction, antibacterial activity, mechanical properties of the composites, changes in the nanotexturas, and a homogeneous distribution of the materials occur, potentiality of its use in more than one application within bone tissue engineering. In the present study it was possible to observe that CHI matrix composites with HA and CNTs present a combination of properties highlighting the potential for application in bone tissue engineering.